Application of Benson Relaxation Technique to Reduce Blood Pressure in Hypertensive Patients at ICCU Ward of RSD Gunung Jati, Cirebon City - Mahfuz, Rizal; Romadhon, Lily Wahyuni (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension, also known as the “silent killer,” is one of the leading causes of death worldwide. Benson relaxation is a non-pharmacological therapy using breathing relaxation combined with the patient’s belief factor. Method: This study used a descriptive method with a case study approach. Result: The application of Benson relaxation for three consecutive days showed a reduction in blood pressure among hypertensive patients. Conclusion: Benson relaxation therapy is effective in reducing blood pressure in patients with hypertension.